Philodendron melloi (Araceae), a new species from central Amazonia, Brazil - Irume, Mariana Victoria; Soares, M. Lourdes; Mayo, Simon Joseph; Carvalho, Rangel Batista de; Zartman, Charles Eugene (Phytotaxa, 2017)
A new species of Philodendron in central Amazonia, Manaus-AM, Brazil, is described and illustrated. Philodendron melloi belongs to the subgenus Philodendron and is possibly a representative of the section Tritomophyllum. This newly described species is similar to P. barrosoanum and P. hyleae, but differs Its preference for terrestrial habitats, persistence of the prophyll, intermediate-sized width of leaf base at the anterior division (1.5-5.6 cm), oblong sinus, floral sympodium with 1-4 inflorescences, 3-6 locules per ovary, and a large number (15-25) of ovules per locule, inserted along the entire length of the placenta.The other two species only have 5 (4-6) and 2 ovules per locule respectively. © 2017 Magnolia Press.